2011
DOI: 10.1364/ol.36.000636
|View full text |Cite
|
Sign up to set email alerts
|

Fiber in-line Mach–Zehnder interferometer constructed by selective infiltration of two air holes in photonic crystal fiber

Abstract: A fiber in-line Mach-Zehnder interferometer is fabricated through selective infiltrating of two adjacent air holes of the innermost layer in the solid core photonic crystal fiber, assisted by femtosecond laser micromachining. The liquid infiltrated has higher refractive index than that of the background silica, and, hence, the two rods created can support a guide mode with lower effective refractive index than that of silica. The interference is produced by the fiber fundamental mode and the guide mode. The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The proposed device is operated as both a directional coupler [1]- [3] and a composite core waveguide [9], [10] of a liquid infiltrated PCF. For a directional coupler, when the phase matching condition is satisfied, light energy is transferred from the core mode into a certain order of rod mode.…”
Section: Device Operation Principle and Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed device is operated as both a directional coupler [1]- [3] and a composite core waveguide [9], [10] of a liquid infiltrated PCF. For a directional coupler, when the phase matching condition is satisfied, light energy is transferred from the core mode into a certain order of rod mode.…”
Section: Device Operation Principle and Fabricationmentioning
confidence: 99%
“…The composite core waveguide model can also be understood from the principle of directional coupler: taking the core and the liquid rod as the two independent waveguides, the mode fields largely overlap due to their small separation, thus the coupling coefficient is increased, which enables mode energy beating and results in an interference fringe pattern over a wide wavelength range. However, the interference fringe pattern produced is usually nonuniform [9], [10], which may be due to the fact that the fundamental core mode simultaneously interferes with different orders of composite waveguide modes 0733-8724/$31.00 © 2012 IEEE as their mode fields are geometrically too close to be separated from each other.…”
Section: Device Operation Principle and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…In an all-fiber MZI made by a fully-liquid filled PCF [7], it was found that the sensing device could have the high sensitivity of -1.83 nm/°C which was 21 times larger than that (∼0.088 nm/°C) of the conventional fiber-based MZI device [9]. The very high temperature sensitivity, ∼7.3 nm/°C, could be obtained by selective liquid infiltration of cladding air holes near the core in a PCF [10]. More recently, the much higher temperature sensitivity of 16.49 nm/°C has been experimentally demonstrated in the in-line fiber MZI made by filling the refractive index liquid into one air hole next to the core of a PCF [11].…”
Section: Introductionmentioning
confidence: 97%
“…In the case of dual-core MOFs, the coupling characteristics between the two cores are strongly dependent on the distance between the two cores, the state of polarization of the guided light, the coupling length, and the normalized frequency Λ/λ (where Λ is the pitch of the air holes and λ is the free space wavelength), which results in an interference fringe pattern appearing in the transmission spectrum. 2 In these structures, when the analyte is inserted into the fiber holes, the device transmittance is modulated by its influence on the coupling between the cores, then the interference fringe pattern shifts, thus RI sensing. [3][4][5][6][7] However, they have also some drawbacks.…”
Section: Introductionmentioning
confidence: 99%